2012
DOI: 10.1111/j.1447-0756.2011.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome microdeletions in Mexican males of couples with idiopathic recurrent pregnancy loss

Abstract: Aim: To analyze the presence of Y chromosome microdeletions in males of Mexican couples with idiopathic recurrent pregnancy losses (RPL). Methods: Seventy-one males from couples with RPL and 66 fertile males as controls were studied. DNA was isolated from peripheral lymphocytes and used to run multiplex polymerase chain reactions. Regions AZFa (sY84, sY86), AZFb (sY127, sY134) and AZFc (sY254, sY255) of the Y chromosome were analyzed according to valid guidelines recommended by the European Academy of Androlog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…[ 165 ] recently evaluated the contribution of Y chromosome microdeletions to RPL in Northeast China, by recruiting 1,072 men with a history of RPL and 971 infertile and 200 fertile males as controls. Their finding did not reveal an association between Y chromosome microdeletions and RPL, which is in accordance with previous studies [ 166 ], [ 167 ], [ 168 ] in Sri Lanka, Mexican and Iran. Till now, many possible explanations, such as selection of sequence-tagged sites (STSs) marker [ 165 ], extraction of DNA from different cells (peripheral blood or spermatozoa) [ 168 ], and sample size [ 163 ], have been suggested for this obvious discrepancy.…”
Section: Maternal and Paternal Genetic Factors Account For Rplsupporting
confidence: 91%
“…[ 165 ] recently evaluated the contribution of Y chromosome microdeletions to RPL in Northeast China, by recruiting 1,072 men with a history of RPL and 971 infertile and 200 fertile males as controls. Their finding did not reveal an association between Y chromosome microdeletions and RPL, which is in accordance with previous studies [ 166 ], [ 167 ], [ 168 ] in Sri Lanka, Mexican and Iran. Till now, many possible explanations, such as selection of sequence-tagged sites (STSs) marker [ 165 ], extraction of DNA from different cells (peripheral blood or spermatozoa) [ 168 ], and sample size [ 163 ], have been suggested for this obvious discrepancy.…”
Section: Maternal and Paternal Genetic Factors Account For Rplsupporting
confidence: 91%
“…Numerous studies have investigated the prevalence of YCM among men whose partner has experienced RPL, however, results were contradictory (70)(71)(72)(73)(74)(75)(76)(77)(78). Of the nine relevant papers, five studies state it is highly unlikely that an association exists between YCM and RPL (72,73,75,76,78). Two of the four papers suggesting an association does exist have been argued against due to their patient selection criteria and methodology which did not conform to the European Academy of Andrology or the European Molecular Genetics Quality Network guidelines (78).…”
Section: Recurrent Pregnancy Lossmentioning
confidence: 99%
“…There are few studies in Mexican populations analyzing the prevalence of Yq deletions in infertile men. Piña et al, studied the presence of Yq microdeletions in Mexican men from couples with recurrent pregnancy loss, they did not find microdeletions 26 . Martinez-Garza S.G, et al found that 12.2% of infertile males had microdeletions of AZFb or AZFc, however they did not analyze gr/gr microdeletions 27 .…”
Section: Discussionmentioning
confidence: 98%